Carbon footprint of Power-to-X derived dimethyl ether using the sorption enhanced DME synthesis process - Styring, Peter; Sanderson, Peter W.; Gell, Isaac; Skorikova, Galina; Sánchez-Martínez, Carlos; Garcia-Garcia, Guillermo; Sluijter, Soraya Nicole (Frontiers in Sustainability, 2022)
Dimethyl ether (DME) could have a promising future as a sustainable diesel fuel replacement as it requires only relatively minor engine modifications. It can be produced from renewable H2 and captured CO2 using Power-to-X technologies. To gain support through the EU Renewable Energy Directive, the production and use of CO2-derived DME as a fuel needs to produce emission savings of at least 70% over the petrodiesel alternative. This study assesses the carbon footprint of producing DME via the sorption-enhanced DME synthesis (SEDMES) process and using it as a transport fuel, compared to producing and using fossil-based petro-diesel. The cradle-to-grave (well-to-wheel) carbon footprint of using DME as a transport fuel is found to be 77% lower than for petrodiesel, if offshore wind power is used for H2 synthesis and DME production. If renewable energy is also used for CO2 capture and waste heat is used for the DME production and purification steps, the DME carbon footprint has the potential to be over 90% lower than that of the fossil-fuel comparator.